ARTIFICIAL INTELLIGENCE AND OPEN SCIENCE IN EDUCATION - Marienko, Maiia; Kovalenko, Valentyna (Physical and Mathematical Education, 2023)
Formulation of the problem. Due to the fact that distance and mixed learning is currently predominant in Ukraine, while it is not always possible to conduct online lessons (due to stabilization or emergency power outages), the problem of diversification and better visualization of the educational material arises. Methodically balanced use of artificial intelligence tools and cloud services of open science can be a possible solution to this problem. Materials and methods. A complex of theoretical research methods was used: comparative and systematic analysis of scientific sources on information technologies to analyze and determine the state of the researched problem of the involvement of open science and artificial intelligence at different levels of education and the study of their interrelationships; verification, synthesis and generalization to build the main theses and provisions of the study; analysis of existing approaches to the use of artificial intelligence in education; assessment of the level of their effectiveness and efficiency. Results. The use and implementation of cloud services of open science will be appropriate in any institutions of general secondary education, institutions of higher education. This will lead to the formation and development of competence in open science at all levels of education. Concepts such as open science, open data, SMART data, FAIR data are in most cases directly related to artificial intelligence. For artificial intelligence and deep learning, labeled and unlabeled datasets become important for machine learning and training artificial intelligence models. The use of artificial intelligence can help students perform routine tasks in the learning process and determine their previous level of preparation. Along with these advantages, there are other serious problems. One of the main and important issues is privacy. Artificial intelligence should be added to the educational materials developed by the teacher. Conclusions. The possibilities of open science enable the new global network generation to discover science and modern knowledge. Artificial intelligence can be used in the educational process as a teacher’s assistant, in addition to being used to create a personalized learning environment and provide feedback to students. For those teachers who are taking the first steps in using artificial intelligence during the lesson, you should pay attention to the images created by artificial intelligence. But there are also risks that can be caused by the use of artificial intelligence in education: the reduction of the role of the teacher, the reduction of creativity and critical thinking skills of students, the risk of increasing the gap between students with high and low socio-economic status.